Additive effects of green tea and coffee on all-cause mortality in patients with type 2 diabetes mellitus: the Fukuoka Diabetes Registry. Issue 1 (21st October 2020) - Komorita, Yuji; Iwase, Masanori; Fujii, Hiroki; Ohkuma, Toshiaki; Ide, Hitoshi; Jodai-Kitamura, Tamaki; Yoshinari, Masahito; Oku, Yutaro; Higashi, Taiki; Nakamura, Udai; Kitazono, Takanari
Abstract : Introduction: The impact of consuming green tea or coffee on mortality in patients with diabetes is controversial. We prospectively investigated the impact of each beverage and their combination on mortality among Japanese patients with type 2 diabetes. Research design and methods: In all, 4923 patients (2790 men, 2133 women) with type 2 diabetes (mean age, 66 years) were followed prospectively (median, 5.3 years; follow-up rate, 99.5%). We evaluated the amount of green tea and coffee consumed using self-administered questionnaires. Results: During the follow-up period, 309 participants died. The consumption of green tea, coffee, and a combination of the beverages was associated with reduced all-cause mortality. Multivariable-adjusted hazard ratios (95% CIs) for green tea were as follows: none 1.0 (referent); 0.85 (0.60–1.22) for ≤1 cup/day; 0.73 (0.51–1.03) for 2–3 cups/day; 0.60 (0.42–0.85) for ≥4 cups/day; and P for trend, 0.002. For coffee, they were: none 1.0 (referent); 0.88 (0.66–1.18) for <1 cup/day; 0.81 (0.58–1.13) for 1 cup/day; 0.59 (0.42–0.82) for ≥2 cups/day; P for trend, 0.002. With the combination they were 1.0 (referent) for no consumption of green tea and coffee; 0.49 (0.24–0.99) for 2–3 cups/day of green tea with ≥2 cups/day of coffee; 0.42 (0.20–0.88) for ≥4 cups/day of green tea with 1 cup/day of coffee; and 0.37 (0.18–0.77) for ≥4 cups/day of green tea with ≥2 cups/day of coffee. Conclusions: Higher consumption of green tea and coffee was associated with reduced all-cause mortality: their combined effect appeared to be additive in patients with type 2 diabetes.